A assistência técnica nos habitats do MST e o papel do arquiteto e urbanista - Cerqueira, Maria Cândida Teixeira de (2009)
This dissertation is about Architect and town planner inserts in the technical support of the Rural establishment and of the possibilities of changes in their habitat. It also looks for its participation through the production of those spaces with or without its performance through two references cases, in Rio Grande do Norte , one called settlement Eldorado de Carajás and another one called Maria da Paz. At first the process represents the model that was adopted systematically by Incra until the middle of the year 2000 with the sub-contracting of their construction work through small companies. These standardized projects which are executed without registration in the system CONFEA/CREA without demand of professional authorship and of technical responsibility of the work. But the process taken place at Maria da Paz s area was configured as one of the first initiatives that stopped with those practices. Consolidated through a partnership among UFRN MST and INCRA/RN, the Architect s technical support and town planner brought new technician-scientific organization and execution of the soil parcels and its habitat. The participation of UFRN was done through a group of studies in land reform and Habitat (GERAH) being this author and coordinator of the methodological proposal, based on the regressive-progressive method and in the inclusion of the conflict as responsible of the ruptures and transductions both done by Henry Léfèbvre and in the research action approached by Carlos Brandão. Therefore it included the process of social learning and collective production of new knowledge and attitudes in relation to the environment in the process called as attended self management in spite of the transformations happened with this new agent s participation. The people re-located to the new areas that got involved in the process and finished their constructions reelaborating the daily practice of the collective effort passed to the self management without technical support. Years later the implantation of those two experiences our research verified that there is a positive image concerning the Architect and town planner, related, most of all to the conception of the activities, orientation and execution of constructions projects and of acceptance of those professionals to the processes of implementation of the Habitats of the Rural establishments. This dissertation analyses this form of performance, from and beyond these images trying to find the professional, specificities or methodological in such a way to demonstrate the importance of its insertion in the formulation and attendance of the more of 100.000 habitats of Rural establishments of the land reform of the country that correspond to most of the housing social interest in the country side